2014
DOI: 10.1007/s12263-013-0382-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional contributions to dementia prevention: main issues on antioxidant micronutrients

Abstract: There is an impressing body of evidence supporting the beneficial role of balanced nutrition in lowering the risk of dementia and its commonest form, Alzheimer's disease. Nevertheless, and despite worldwide dementia epidemic, there is much unfounded skepticism and lack of information among physicians. As a result, the diagnosis of cognitive impairment occurs still far too late, at best symptomatic drugs keep being prescribed and patients and caregivers are left with little concrete support in the hands of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…[57][58][59][60][61][62] A recent metaanalysis of 7 studies on dietary intakes of vitamin E, vitamin C, and beta carotene confirmed a relative risk for the development of Alzheimer disease of 0.76 for vitamin E, 0.83 for vitamin C, and 0.88 for beta carotene. 63 A trial of vitamin E in 341 patients with moderate to severe Alzheimer disease 64 treated with a daily dose of 2000 IU of vitamin E for 2 years showed a significant delay in Alzheimer disease progression and in nursing home placement compared with placebo.…”
Section: Diet and Nutritionmentioning
confidence: 99%
“…[57][58][59][60][61][62] A recent metaanalysis of 7 studies on dietary intakes of vitamin E, vitamin C, and beta carotene confirmed a relative risk for the development of Alzheimer disease of 0.76 for vitamin E, 0.83 for vitamin C, and 0.88 for beta carotene. 63 A trial of vitamin E in 341 patients with moderate to severe Alzheimer disease 64 treated with a daily dose of 2000 IU of vitamin E for 2 years showed a significant delay in Alzheimer disease progression and in nursing home placement compared with placebo.…”
Section: Diet and Nutritionmentioning
confidence: 99%
“…It is a promising development that preventing cognitive decline or improving its function has been shown effectively through medical and nutritional interventions (Polidori and Schulz, 2014). AD accounts for 60-80% of dementia cases and is the most common form of dementia.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…M. Cristina Polidori at the University Hospital of Cologne and her colleagues have been at the forefront of this research. Dr. Polidori has reported that Western diets generally favor saturated fat intake which can increase Alzheimer risk [69]. Part of the remedy is to replace fish for meat and consume high amounts of fruits, vegetables, fresh dairy products, and plant-based fats and 138 12 Conditions That Can Promote Alzheimer's nuts [69].…”
Section: Hyperlipidemiamentioning
confidence: 99%
“…Dr. Polidori has reported that Western diets generally favor saturated fat intake which can increase Alzheimer risk [69]. Part of the remedy is to replace fish for meat and consume high amounts of fruits, vegetables, fresh dairy products, and plant-based fats and 138 12 Conditions That Can Promote Alzheimer's nuts [69]. Other food alternatives include replacing the saturated fat contained in butter or margarine with olive oil and salt with herbs and spices to flavor food.…”
Section: Hyperlipidemiamentioning
confidence: 99%